The use of topical metronidazole in the management of seborrheic dermatitis – a systematic review and meta-analysis of randomized controlled trials - Lee, E. Lyn; Shanmugham, Suresh; Kumar, Suresh; Smales, Frederick Charles; Ching, Siew Mooi; Veettil, Sajesh K. (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Topical metronidazole, with its well-known anti-inflammatory and antibacterial properties, could be beneficial for managing seborrheic dermatitis (SD), but studies report conflicting results. The aim was to evaluate the efficacy and safety of topical metronidazole in the treatment of SD. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A systematic search of Medline, Embase, and CENTRAL was conducted from inception to April 2024. Randomized controlled trials (RCTs) comparing metronidazole to any comparator for SD were included in this study. Data were pooled using random-effects models. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. Seven RCTs were included. Overall, topical metronidazole did not significantly reduce SD symptom severity when compared to any comparator/treatment. However, it significantly reduced symptom severity compared to placebo after 4 to 8 weeks (standardized mean difference (SMD) -3.00, 95% CI, -5.21 to -0.78). Specifically for facial SD, metronidazole showed significant symptom reduction (SMD -0.85, 95% CI, -1.41 to -0.29). No significant differences were found in the proportion of patients with clinical improvement or side effect frequency. Most studies had a high risk of bias and lacked information on missing data and assessor masking. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Topical metronidazole demonstrates potential for managing SD, but current trials lack quality. Larger, high-quality trials are needed to confirm its efficacy and compare it with other treatments for SD.